JAVANESE CALENDAR CALCULATION AND FATE DETERMINATION:: A Study of the People of Aek Raso Village, Torgamba Sub-District, South Labuhanbatu District - Fauziyah, Dwi; Naldo, Jufri; Siregar, Husna Sari (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2024)
The Javanese calendar is a calendar that contains complete market days that have certain values or meanings called neptu. The people of Aek Raso village are people who consider the day as something sacred, especially the day on which a person was born. Because the day on which a person was born is used for various calculations of a desire or desire, such as determining a mate, marriage, circumcision and searching for lost items. The purpose of this study is to analyse how Javanese calculation beliefs and fate determinants. Descriptive method, data collection techniques used are observation techniques, literature, interviews and documentation. The analysis technique used is qualitative method. The result of the analysis of this research is that the people of Aek Raso village, Torgamba sub- district, Labuhanbatu Selatan Regency still believe or uphold the tradition in the calculation of the Javanese calendar in determining life. Some people believe in the truth of calendar calculations and still practice them. It can be said that some people want to have a better life. Local people say that they respect and will continue to preserve the traditions inherited from their ancestors. However, the community considers the calculation of the Javanese calendar as just a tradition and not as worship.